Sex differences in risk factors for myocardial infarction: cohort study of UK Biobank participants - Millett, E; Peters, S; Woodward, M (BMJ Publishing Group, 2018)
Objectives To investigate sex differences in risk factor associations with incident myocardial infarction (MI) and whether these vary by age. Design Prospective population based study. Setting UK Biobank Participants 471,998 participants, (56% women; mean age 56.2 years) with no history of cardiovascular disease. Main outcome measures Incident (fatal and non-fatal) MI. Results 5,081 participants (29% women) experienced MI over seven years mean follow-up, resulting in incidence rates of 7.76/10,000 person years (95% CI 7.37 to 8.16) among women and 24.35/10,000 (23.57 to 25.16) among men. In both sexes, higher blood pressure (BP) indices, smoking intensity, and body mass index, and the presence of diabetes were associated with an increased risk of MI, but associations were attenuated with age. Compared with men, women had an excess HR of MI for systolic BP and hypertension, smoking status and intensity, and diabetes: ratio of HRs (95% CIs) were 1.09 (1.02 to 1.16) for systolic BP, 1.55 (1.32 to 1.83) for current smoking, and 2.91 (1.56 to 5.45) for type I and 1.47 (1.16 to 1.87) for type II diabetes. There was no evidence of attenuation of any of these RHRs with age (p>0.2). With the exception of type I diabetes, for all risk factors, and for every category of those risk factors, men had higher rates of MI than women. Conclusions Rates of MI are higher among men than women. However, several major risk factors for MI confer an excess relative risk of MI among women compared with men. With ageing, sex-specific associations decline but, where it occurs, the female disadvantage in relative risk persists. Over time, population ageing, coupled with the increasing prevalence of lifestyle-associated risk factors, is likely to result in women having a more similar rate of MI to men.